2008
DOI: 10.1080/15205430802375311
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Person Perceptions: Comparing Four Common Statistical Approaches to Third-Person Research

Abstract: This article addresses whether current methods of measurement are sufficient to reflect all nuances of the third-person effect. We do so by content analyzing all major third-person effect (3PE) articles, assessing measurement and analysis approaches employed by 3PE researchers. We revisit data from two published studies, comparing analytical models that emerged as commonly used by 3PE researchers (i.e., the standard subtractive measure, Whitt's Diamond model, first-and third-person estimates entered separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 41 publications
(36 reference statements)
1
39
0
1
Order By: Relevance
“…When a positive correlation components is present, a modest positive correlation (as a rule of thumb, less than .5 but greater than .1) is less harmful to the reliability of the difference score. Schmierbach et al (2008) once expressed their uncertainty about "whether the diamond model…conclusively addresses the potential problem that a significant subtractive term might really reflect variance due entirely to perceived effects on self or other in isolation." The present paper has discovered the problems associated with this model.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…When a positive correlation components is present, a modest positive correlation (as a rule of thumb, less than .5 but greater than .1) is less harmful to the reliability of the difference score. Schmierbach et al (2008) once expressed their uncertainty about "whether the diamond model…conclusively addresses the potential problem that a significant subtractive term might really reflect variance due entirely to perceived effects on self or other in isolation." The present paper has discovered the problems associated with this model.…”
Section: Discussionmentioning
confidence: 97%
“…A number of past studies (Edwards, 2002;Gunther, 1998;Salwen, 1998) have specifically questioned the use of difference scores to test the perceived media effects on behavioral outcomes. Schmierbach et al (2008) held that the subtractive measurement of difference scores might mask the real influence on support for censorship and that it potentially confounds relative difference with the absolute level of the variables in question. Lo and Wei (2002) also suggested that the inconsistency was largely due to the inappropriate use of perceptual bias as a predictor.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 3 more Smart Citations